RISIKO PRODUKSI AYAM BROILER DAN PREFERENSI PETERNAK DI KABUPATEN BEKASI - Gita Vinanda; Harianto Harianto; Lukytawati Anggraeni (Jurnal Manajemen & Agribisnis, 2016)
Broiler farms are dealing with many risks, especially the risk of production due to the mortality. This study aimed to: 1) analyze the factors that affect the production of broiler chickens, 2) analyze the risks faced by broiler farmers, and 3) analyze the risk preferences of production. This study used two business patterns of broiler chicken farms, i.e. cooperation/partnership and independent. This study was conducted in Bekasi, a research area which was intentionally chosen in a consideration that the area hasg a positive population trend. There were 74 breeders involved in this study. The analysis was conducted by using Just Pope function model and utility maximization. The results suggest that the factors affecting broiler production include feeds and husks for the independent farmers. Feeds, vaccines and density are influential variables for production by the cooperative farmers. The variables that increase the production risks in the independent farmers include vaccines, labor, and husk, while the variable affecting the cooperative farmers is labor. The variable that can minimize risks for the independent farmers is feeds, while for the cooperative farmers, the variable is vaccine. The risk preference of the independent farmers on the overall input usage is the risk averse or a tendency to avoid risk. Broiler chicken farms require a counseling to improve their quality of human resources, accurate schedule of vaccine applications, and attention to husk condition in order to reduce risks.Keywords: production risk, preferences, just and pope, broiler farms